Música dos espaços: paisagem sonora do Nordeste no movimento armorial - Ventura, Leonardo Carneiro (2007)
This work exams the presence of music in the imaginary constitution of spaces, taking as study s object part of the musical production of the Armorial Movement, officially casted in 1970 in the city of Recife, Pernambuco. From that so called, by the Armorial s discourse, the essence of the brazilian northeastern popular art , the armorialists has intended to make an art that express an idea of northeasternity and brazility . Tries to demonstrate how the music has exerted a basic function of condensation and spreading of the armorial aesthetics, auditorily delimiting the territory of Brazilian Northeastern and, at the same time, trying to impose a sonority to it. This work still analyses the elaboration of what would be a proper soundscape of the Northeastern and how this elaboration passes trough the desire of crystallization of an idealized space, perpetual, escape line of the characteristic modernizing and postmodernizing experience of the twentieth century, product, in turn, of the anxiety of conservation of the Northeastern as a shelter to the traditions that has been evidenced by the construction of an visibility and, also, an audibility to the so called northeastern universe. It analyses, too, the way as works the confrontation between the idea of a so called northeastern soundscape - sonorous events set taken as typical from the rural space - and a sonorous archives series produced since 1920 with the regionalist discourse, showing how was elaborated an armorial music that has intended to represent the brazilian Northeastern. It evidences how, to the elaboration of armorial music, it was managed elements from the European musical culture so called scholar. It argues that the utilization of, to the manufacture of the armorial thinking and aesthetics, of a European mimical capital, so called that way by Stephen Greenblat, was consequence of the intellectual leadership of the Movement, centered in the writer Ariano Suassuna. It argues that Suassuna, followed by the musicians and the artists of the Movement, has searched to evidence a genetic linking between what he has considered the Brazilian true popular art and the medieval Iberian culture. For in such a way, the music was taken as a formation element of the social imaginary and directed to verify a relationship between the Northeastern idealized by the Armorial and the music produced by the Movement. This work has searched, therefore, through the analysis of the armorial music, to study the possible confluences between music and the space that has produced it to, by this analysis, to think the complicity between music and history